2007
DOI: 10.1017/s1368980007223870
|View full text |Cite
|
Sign up to set email alerts
|

Developing nutrient profile models: a systematic approach

Abstract: Objective: Nutrient profiling can be defined as the 'the science of categorising foods according to their nutritional composition'. The purpose of the present paper is to describe a systematic and logical approach to nutrient profiling. Design: A seven-stage decision-making process is proposed and, as an illustration of how the approach might operate in practice, the development of a nutrient profiling model for the purpose of highlighting breakfast cereals that are 'high in fat, sugar or salt' is described. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 4 publications
0
102
0
8
Order By: Relevance
“…Thus, profiling systems should not be too nutritionally stringent, and policy makers should consider the social and dietary implications if only the most healthy foods are permitted in some settings such as schools. During profile development, scientific and practical criteria should be used to systematically consider the purpose of systems, their target population, the model type (across-the-board or category-specific), which nutrients or other food components to consider, reference amounts (per 100 g, 100 kJ/100 kcal or per serving), scoring systems (continuous or categorical) and threshold levels for nutrients (29) . The selection of reference amounts is particularly important and strongly influences final food rankings (30) .…”
Section: Differences Among Nutrient Profiling Schemesmentioning
confidence: 99%
“…Thus, profiling systems should not be too nutritionally stringent, and policy makers should consider the social and dietary implications if only the most healthy foods are permitted in some settings such as schools. During profile development, scientific and practical criteria should be used to systematically consider the purpose of systems, their target population, the model type (across-the-board or category-specific), which nutrients or other food components to consider, reference amounts (per 100 g, 100 kJ/100 kcal or per serving), scoring systems (continuous or categorical) and threshold levels for nutrients (29) . The selection of reference amounts is particularly important and strongly influences final food rankings (30) .…”
Section: Differences Among Nutrient Profiling Schemesmentioning
confidence: 99%
“…11,12 For example, when comparing eight executions of FoP calorie flags, Van Kleef et al 5 reported that consumers found the 'calories per serving flag' option to be most preferable but only under the condition that the portion was perceived to represent a realistic and easy-to-understand consumption unit. There is on-going debate as to whether nutrition information is best presented 'per 100 g/100 ml' or 'per portion' 8,13,14 particularly amongst those concerned with the development of nutrient profiling models which attempt to define 'healthy' versus 'unhealthy' foods. Many consider that 100 g/100 ml best serves as a comparator between foods that are often presented in a range of different portion sizes, whereas others argue that a food containing high levels of an 'unhealthy' nutrient 'per 100 g' may only make a small negative contribution to a person's diet if the 'typical' portion for that food is much smaller than 100 g. 13 Product category associations (e.g., nutrition value of chocolate versus yogurt) have been shown to be one of the cues used by consumers to form judgements about a product's healthfulness.…”
Section: Introductionmentioning
confidence: 99%
“…There is on-going debate as to whether nutrition information is best presented 'per 100 g/100 ml' or 'per portion' 8,13,14 particularly amongst those concerned with the development of nutrient profiling models which attempt to define 'healthy' versus 'unhealthy' foods. Many consider that 100 g/100 ml best serves as a comparator between foods that are often presented in a range of different portion sizes, whereas others argue that a food containing high levels of an 'unhealthy' nutrient 'per 100 g' may only make a small negative contribution to a person's diet if the 'typical' portion for that food is much smaller than 100 g. 13 Product category associations (e.g., nutrition value of chocolate versus yogurt) have been shown to be one of the cues used by consumers to form judgements about a product's healthfulness. 15,16 On the basis of the evaluability principle, it is also argued that 'numerical [nutrient content] information lacks meaning by itself and has to be compared with other information to be interpreted meaningfully'.…”
Section: Introductionmentioning
confidence: 99%
“…Citing the improvement of public health as a primary objective, numerous studies have highlighted the need for a nutritional scoring system that is both comprehensive in its coverage of food products and easily understood by consumers [1][2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%